Prescription of Extended-Duration Thromboprophylaxis after High-Risk, Abdominopelvic Cancer Surgery - Wright, Jason D. (Gynecol Oncol, 2016)
OBJECTIVE: Extended-duration thromboprophylaxis for 4 weeks after discharge has been demonstrated to reduce venous thromboembolic events (VTE) in cancer patients undergoing abdominopelvic surgery and is recommended in national guidelines. We examined the utilization and effectiveness of extended-duration low molecular weight heparin prophylaxis in high-risk cancer patients. METHODS: We analyzed patients with colon, ovarian, and uterine cancer who underwent surgery from 2009–2013 and who were recorded in the MarketScan database. Multivariable models and propensity score analysis with inverse probability of treatment weight were developed to examine uptake and predictors of use of post-discharge low molecular weight heparin (LMWH), as well as associated adverse events (transfusion, and hemorrhage). RESULTS: A total of 63,280 patients were identified. Use of extended-duration prophylaxis increased from 2009 to 2013 from 1.4% to 1.7% (P=0.67) for colectomy, 5.9% to 18.3% for ovarian cancer surgery (P<0.001), and 6.3% to 12.2% (P<0.001) for hysterectomy for endometrial cancer. There was no association between use of extended-duration prophylaxis and reductions in VTE for any of the procedures: colectomy (2.4% with extended-duration prophylaxis vs. 2.9% without prophylaxis, OR=0.84; 95% CI, 0.54-1.31), ovarian cancer-directed surgery (3.7% vs. 3.6%, OR=1.01; 95% CI, 0.76-1.33), hysterectomy (2.1% vs. 2.1%; OR=0.96; 95% CI, 0.67-1.38). Extended-duration prophylaxis was associated with an increased risk of adverse postoperative events: 2.20 (95% CI, 1.51-3.19) after colectomy, 1.24 (95% CI, 0.92-1.68) following ovarian cancer-directed surgery and 0.99 (95% CI, 0.66-1.48) for hysterectomy for endometrial cancer. CONCLUSION: Use of extended-duration thromboprophylaxis is low among high-risk cancer patients undergoing surgery.